2008
DOI: 10.1016/j.neuron.2008.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Translation Initiation Factor eIF2α Increases BACE1 Levels and Promotes Amyloidogenesis

Abstract: Summary Beta-site APP cleaving enzyme-1 (BACE1), the rate-limiting enzyme for β-amyloid (Aβ) production, is elevated in Alzheimer’s disease (AD). Here, we show that energy deprivation induces phosphorylation of the translation initiation factor eIF2α eIF2α-P), which increases the translation of BACE1. Salubrinal, an inhibitor of eIF2α-P phosphatase PP1c, directly increases BACE1 and elevates Aβ production in primary neurons. Preventing eIF2α phosphorylation by transfection with constitutively active PP1c regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
348
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(386 citation statements)
references
References 113 publications
(201 reference statements)
31
348
3
1
Order By: Relevance
“…First, it is possible that pharmacological approaches with the potent agonist 7,8-DHF may activate BDNF-TrkB signaling more efficiently than gene delivery or stem cell strategies. Furthermore, previous studies from our laboratory and others have demonstrated that elevations in BACE1 have an important role in accelerating disease progression in 5XFAD mouse brains (Devi and Ohno, 2010b;O'Connor et al, 2008;Ohno et al, 2007;Zhang et al, 2009;Zhao et al, 2007) as well as in sporadic AD brains (Fukumoto et al, 2002;Li et al, 2004;Yang et al, 2003).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…First, it is possible that pharmacological approaches with the potent agonist 7,8-DHF may activate BDNF-TrkB signaling more efficiently than gene delivery or stem cell strategies. Furthermore, previous studies from our laboratory and others have demonstrated that elevations in BACE1 have an important role in accelerating disease progression in 5XFAD mouse brains (Devi and Ohno, 2010b;O'Connor et al, 2008;Ohno et al, 2007;Zhang et al, 2009;Zhao et al, 2007) as well as in sporadic AD brains (Fukumoto et al, 2002;Li et al, 2004;Yang et al, 2003).…”
Section: Discussionmentioning
confidence: 82%
“…Multiple mechanisms are recently proposed to mediate the upregulation of BACE1 associated with AD. Those include the increased phosphorylation of the translation initiation factor eIF2a Devi and Ohno, 2010b;O'Connor et al, 2008), caspase-3-dependent inactivation of GGA3 leading to decreased lysosomal degradation of BACE1 (Sarajarvi et al, 2009;Tesco et al, 2007), changes in microRNA expression profiles (Hebert et al, 2008;Wang et al, 2008), p25/cyclin-dependent kinase 5 pathways (Cruz et al, 2006;Wen et al, 2008), calpain activation (Liang et al, 2010), the receptor for advanced glycation end products (RAGE) (Cho et al, 2009;Guglielmotto et al, 2010), and oxidative stress or related signals such as nuclear factor-kB, c-Jun N-terminal kinase, and p38 MAPK (Chen et al, 2011;Chen et al, 2008;Coma et al, 2008;Xiong et al, 2007). Further study will be needed to determine the molecular pathways by which activation of BDNF-TrkB signaling may counteract the BACE1 elevation in 5XFAD mice.…”
Section: Discussionmentioning
confidence: 99%
“…reported that Aβ levels were significantly increased suggesting for the first time that energy deprivation acts as an amyloidogenic stimulus in vivo (Velliquette et al ., 2005). In a later paper that used glucose deprivation in cell culture as a model of energy deficiency, it was demonstrated a post‐transcriptional increase in BACE1 level and enhanced Aβ production (O'Connor et al ., 2008). This effect was then confirmed in two APP transgenic mouse models (i.e., Tg2576 and 5xFAD mice) in which pharmacological energy deprivation promoted amyloidogenesis via a BACE‐1‐dependent mechanism (O'Connor et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this concept, previous studies have demonstrated that using a pharmacological model of energy metabolism inhibition in APP overexpressing transgenic mice (i.e., Tg2576), BACE‐1 and Aβ levels become elevated, suggesting that energy deprivation may be amyloidogenic in vivo (O'Connor et al ., 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Those findings are also consistent with animal models for AD [37,38] and Tau was shown to interfere with ER-associated degradation (ERAD). In addition, eIF2α phosphorylation modulates BACE-1 expression in AD mice [39]. ATF4 was also shown to regulate gamma-secretase activity during amino acid imbalance, which triggers ER stress, also favouring amyloidogenic pathway [40].…”
Section: Gene4c Muta4onsmentioning
confidence: 99%